Use of soil and climate data to assess the risk of agricultural drought for policy support in Europe. - Zdruli, Pandi; Jones, Robert J. A.; Montanarella, Luca (INRA / EDP Sciences, 2001)
This paper describes the use of soil and climatic data for assessing the risk of drought in Europe. Soil moisture regimes are defined for soil classification purposes and these can be used to delineate areas with the same type of soil climate. Maps showing the distribution of arid soils in USA and dry areas in Southern Europe are presented. In the case of agricultural drought, it is the soil water available to plants (SWAP) that is the most important soil factor in assessing this risk and a simple model for estimating this is described. This model can be linked to spatial and point data from the European Soil Database. In the absence of sufficient soil water retention measurements, preliminary maps of SWAP in Europe have been produced using pedotransfer rules. The study concludes that basic soil maps can be used to identify some areas where agricultural drought is likely to be a problem. However more precise modelling of droughtiness, based on interactions of soil available water with the average soil moisture deficit, estimated from meteorological data, is needed, to support policy making today.
Keywords: soil; climate; drought; risk; policy; Europe